GWP, AP, and EP Contribution on Potential Improving Scenarios of Domestic SWM in Padang City: A Review - Suci Wulandari; Slamet Raharjo (Universitas Diponegoro, 2021)
The increase in solid waste generation is incompatible with solid waste management (SWM). Padang city have a small processing percentage of 5% through composting and recyling. Improper and nonoptimal SWM lead to many obstacles including climate change, water and soil contamination, to creatures life disturbance. By conducting Impact Assessment and Contribution Analysis, this study examines the most impact contributor of unit processes in four scenarios of domestic solid waste management in Padang City. Scenario 0 presents the existing condition; scenarios 1, 2, and 3 present the improvement of Scenario 0 in recycling percentage rate and technology implementation in a row by composting, incineration, and anaerobic digestion. CML2001, impact assessment method by Center of Environmental Sciences of Leiden University, is used to assess the environmental impact of Global Warming Potential (GWP), Acidification Potential (AP), and Eutrophication Potential (EP). This study found that the significant impact for the four scenarios is GWP by the contribution percentage over 72%. While EP is the second place in the contribution range of 1.70% to 5.46%, and followed by AP under 0.91%. Scenario 1 is the best scenario due to the small contribution of impact compared to other scernarios, and potentially to be applied by modification in increase of composting percentage and additional recovery gas in landfill.